Analisis model pembangunan pertanian dan transformasi yang terjadi di Desa Gedangan, Kecamatan Cepogo, Kabupaten Boyolali - Antriyandarti, Ernoiz; Ardila, Insyirah Ayu; Syarif, Jadid Adrian; Agustin, Laily; Cahyani, Latifah Dita; Panemuan, Rizki Guntur; Nugroho, Sasmito Agung (Institute of Advance Science, Social, and Sustainable Future, 2024)
Introduction: Desa Gedangan serves as the rural center in Cepogo District, Boyolali. Situated 14 km west of the downtown area of Boyolali Regency, it stands as a prominent vegetable-producing village in the region. The potential of Desa Gedangan lies in its rural tourism, encompassing attractions such as Candi Sari, Candi Lawang, Pasar Ngatpaingan, and agricultural activities. Challenges faced by Desa Gedangan include issues regarding the development of tourism infrastructure and pest control in the vegetable farming sector. Structural transformation in Desa Gedangan primarily focuses on the agricultural sector, which continues to evolve and is optimized to support the village's economy. Method: The fundamental methodology employed in this research is descriptive analytical with a qualitative approach, conducted through a case study in Desa Gedangan, Cepogo District, Boyolali Regency. Data sources comprise both primary and secondary data. Result: Primary data is obtained from key informants, primarily through direct interviews with the village head. Secondary data consists of evidence, records, or historical reports archived as documentary data. Findings reveal that institutional transformation in Desa Gedangan is currently limited due to adherence to regulations at the district level. The existing institutional transformation is mainly observed within the Karang Taruna organization. Technological transformation in Desa Gedangan involves the construction of three biogas reactors consisting of three ponds, established through collaboration with the Agricultural Technology Development Institute. The agricultural development model in Desa Gedangan currently emphasizes diversification of agricultural products, as evidenced by the cultivation of tobacco for commercial purpose.